The Effect of Competence and Compensation on Performance with Job Satisfaction as an Intervening Variable - Wulansari, Sri (Jurnal Manajemen (Edisi Elektronik), 2025)
This study was motivated by the phenomenon of declining performance of agricultural extension workers at the Kulon Progo Regency Agriculture and Food Service Office, which was influenced by compensation discrepancies and less than optimal competency development. This study aims to analyse the effect of competence and compensation on performance with job satisfaction as an intervening variable. The method used is a quantitative approach with a sample of 140 respondents determined through the Slovin formula and Accidental Sampling technique. The results showed that competence and compensation have a significant positive effect on performance, both directly and through job satisfaction. Job satisfaction proved to be an important link that strengthens the influence of competence and compensation on the performance of extension workers. The implications of these results emphasise the need for continuous competency development and fair compensation to improve extension worker satisfaction and performance. This research provides insights for policy makers to design more effective human resource management strategies in supporting the productivity of the agricultural sector in Kulon Progo.